Multimodal approach to the diagnosis of pure neural neuropathy in leprosy - Spitz, Clarissa Neves; Pitta, Izabela Jardim Rodrigues; Versiani, Isadora; Sales, Anna Maria; de Sousa, Ana Caroline Siquara; Hacker, Mariana Andrea; Sarno, Euzenir Nunes; Pinheiro, Roberta Olmo; Jardim, Marcia Rodrigues (Frontiers in Medicine, 2025)
IntroductionNeuropathy is an important feature of leprosy, a chronic infection caused by Mycobacterium leprae that mainly affects the skin and peripheral nerves. There is a rare and atypical form called the pure neural form, which is manifested only by changes in the nerves, without lesions on the skin, which makes early diagnosis difficult. If left untreated, neuropathy can lead to deformities and disabilities.MethodsNerve conduction studies, ultrasound and histopathology by nerve biopsy (gold standard).ResultsThis study evaluated 29 cases that underwent peripheral nerve biopsy, which were then divided into positive or negative groups for pure neural form. The analysis sought to identify patterns that would help differentiate this form of leprosy, through clinical, electrophysiological and ultrasound evaluations. Of the 29 patients included, 13 were diagnosed with pure neural form and 16 were not.DiscussionThe clinical features: sensory involvement occurred in all cases of confirmed pure neural form, while weakness was noted in the majority of cases in both groups, neural thickening was seen more frequently in the positive cases. Neurophysiology: sensory involvement was observed in all cases, motor involvement, a similar distribution was observed between the two groups (patterns were analyzed). On Ultrasound, neural thickening was observed in both groups, hypoechogenicity and heterogeneous fascicular disarray more frequent in the group with the diagnosis, flow in the Power Doppler in two patients only in pure neural form positive. There were no statistically significant differences in the clinical-electrophysiological and ultrasound analysis. With regard to the histopathological findings, bacilliferous findings were observed in 11 and inflammatory findings in 2. The characteristics of the negative cases were also analyzed. Pure neural leprosy remains a diagnostic challenge, especially in areas with limited resources. Histopathological examination remains the gold standard and, although non-invasive methods are desirable, they require rigorous validation to ensure accuracy.